Drug Repurposing of Loratadine as a DNMT1 Inhibitor: Comparative Evaluation with Cisplatin in Patient-Derived Oral Squamous Cell Carcinoma Cells (Precision Medicine Communications, 2024)
Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer, with a low overall survival rate due to altered epigenetic regulation, specifically DNA hypermethylation mediated by DNA methyltransferase 1 (DNMT1). Inhibitors of DNMT1 are promising compounds for cancer treatment and research. In this study, repurposed drugs, including Loratadine, were virtually screened through molecular docking to select the drug with the highest interaction with the DNMT1 protein. Loratadine demonstrated maximum drug-like characteristics, making it a promising treatment option for OSCC patients. Furthermore, for experimental validation, we investigated the cytotoxicity of Loratadine, Cisplatin, and their combination against primary oral squamous cell carcinoma cells. The MTT assays revealed that Loratadine and Cisplatin each had a time and dose-dependent inhibitory impact, with 50% inhibitory concentrations (IC50) of 86.78 µM and 67.05 µM, respectively. The combination of both drugs had an additive effect against OSCC cells, with an IC50 of 52.05 µM. However, the apoptosis assay results revealed that treatment with loratadine had no significant effect on cell viability in OSCC. These findings suggest that Loratadine likely has anti-cancer effects but kills or inhibits cells at various dosages, independently of apoptosis. Further mechanistic studies are needed.
Keywords: Loratadine; cisplatin; drug repurposing; OSSC; DNMT1; Molecular Docking